Face Transplantation: Partial Graft Loss of the First Case 10 Years Later. Issue 7 (9th March 2017) - Morelon, E.; Petruzzo, P.; Kanitakis, J.; Dakpé, S.; Thaunat, O.; Dubois, V.; Choukroun, G.; Testelin, S.; Dubernard, J.‐M.; Badet, L.; Devauchelle, B.
Abstract : Ten years after the first face transplantation, we report the partial loss of this graft. After two episodes of acute rejection (AR) occurred and completely reversed in the first posttransplantation year, at 90 months posttransplantation the patient developed de novo class II donor‐specific antibodies, without clinical signs of AR. Some months later, she developed several skin rejection episodes treated with steroid pulses. Despite rapid clinical improvement, some months later the sentinel skin graft underwent necrosis. Microscopic examination showed intimal thickening, thrombosis of the pedicle vessel, and C4d deposits on the endothelium of some dermal vessels of the facial graft. Flow magnetic resonance imaging of the facial graft showed a decrease of the distal right facial artery flow. Three steroid pulses of 500 mg each, followed by intravenous immunoglobulins (2 g/kg), five sessions of plasmapheresis, and three cycles of bortezomib 1.3 mg/m 2, were administered. Despite rescue therapy with eculizumab, necrosis of the lips and the perioral area occurred, which led to surgical removal of the lower lip, labial commissures, and part of the right cheek in May 2015. In January 2016, the patient underwent conventional facial reconstruction because during the retransplantation evaluation a small‐cell lung carcinoma was discovered, causing the patient's death in April 2016. Abstract : The authors report the partial graft loss of the first face transplantation performed in 2005, after humoral rejection. See the editorial from Krezdorn and Pomahac onpage 1703 .